For big comparison: Why the arguments against comparing entire religious traditions fail - Decosimo, Joseph David (Religion compass, 2018)
The nearly unanimous scholarly consensus is that one should not compare entire religious traditions. Big comparison, we're told, is vague, unilluminating, and misleading. And this is because religions are just too big and internally diverse to helpfully compare. Worse, big comparison implicates and extends the essentialist and colonialist legacies of the field's origins. This article contends that such arguments fail, and it argues for the inevitability of big comparison and the possibility and value of executing such comparison well. The patterns of thought in virtue of which big comparison is rejected are not only part and parcel of responsible interpretation but a consequence of commitment to holism. Engaging recent philosophical work on generics and considering the way concepts like race can enable illuminating comparison such as those involved in discourse about value gaps between white and black lives, I further argue that matters are not saliently different when it comes to comparing under categories like Judaism or Buddhism. As racial categories admit of useful and problematic comparative usage, so too religious categories. I conclude by offering several snapshots of fruitful big comparison and showing that the case against big comparison itself depends on the very modes of thought it wishes to proscribe.